The Effect of the Corrosion Medium on Silane Coatings Deposited on Titanium Grade 2 and Titanium Alloy Ti13Nb13Zr - Oliwia Kierat (MDPI AG, 2021)
The present paper focuses on the fabrication of coatings based on vinyltrimethoxysilane and the influence of various corrosion media on the coatings produced. Coatings were deposited on two substrate materials, namely, titanium Grade 2 and titanium alloy Ti13Nb13Zr, by immersion in a solution containing vinyltrimethoxysilane, anhydrous ethyl alcohol, acetic acid and distilled water. The obtained coatings were characterized in terms of surface morphology, adhesion to the substrate and corrosion resistance. As corrosion solutions, four different simulated physiological fluids, which differed in the contents of individual ions, and a 1 mol dm−3 NaBr solution were used. The chloride ions contained in the simulated physiological fluids did not lead to pitting corrosion of titanium Grade 2 and titanium alloy Ti13Nb13Zr. This investigation shows that titanium undergoes pitting corrosion in a bromide ion medium. It is demonstrated that the investigated coatings slow down corrosion processes in all corrosion media examined.